Topsoil and subsoil phosphorus dynamics: evidence from long-term experiments - Dolan, Samantha (2019)
Phosphate rock is the main source of phosphorus (P) in agricultural fertilisers; global stocks are finite and are required for future food security. Long-term use of P fertilisers results in the accumulation of residual P in agricultural soils and utilising these resources will improve sustainability of P use and may lead to environmental benefits. Subsoil P reserves may be an important source of plant-available P however current fertiliser recommendations are based on topsoil P only. Therefore, the aim of this project was to understand topsoil and subsoil P dynamics in long-term experiments and the factors influencing the accumulation (Chapter 3), plant-availability (Chapter 4), solubility (Chapter 5), lability (Chapter 6) and cycling and transfer (Chapter 7) of phosphate in soil. To this end, two long-term field experiments managed by Scotland’s Rural College in Craibstone, Aberdeenshire, were utilised. The ‘Old Rotation’, established in 1922, has a series of plots subject to different NPK fertiliser strategies and the ‘pH Rotation’, established in 1961, consists of plots in which soil pH is controlled to cover the range 4.5 to 7.5, in increments of 0.5 pH units. Topsoils (0 to 20 cm) and subsoils (20 to 40 cm) were collected in February 2015 post-harvest and prior to tillage and fertiliser application. The effects of soil pH control, fertiliser management strategy and cropping on P dynamics were investigated.